Breaking the mold: Thoughts on Punjab's future economic development - Nirvikar Singh (University of California, Economics Department, 2015)
The economy of Punjab state in India offers an interesting case study. Punjab has been for decades - and remains - one of India's better-off states, and so it tends not be included in the primary focus of national programs meant to reduce poverty or spur economic development. But, Punjab's relative economic position within India has declined rapidly in recent years. This decline has been accompanied by environmental problems and symptoms of deep social malaise. As will be argued in this paper, Punjab is facing a multidimensional crisis that requires urgent attention. This paper provides an overview of Punjab's crisis, through an analysis of the dynamics of Punjab's economic development as shaped by its political economy, its social dynamics and exogenous events since independence. It argues that one can understand both Punjab's success in certain areas of agriculture and its subsequent relative decline in terms of the interaction of these factors. It uses this historical analysis to provide an assessment of Punjab's future economic development, in terms of the structural changes that are needed, and how these can be encouraged or implemented by policy makers within the constraints of its current political-economic equilibrium.
Keywords: O10; O20; P16; P26; 330; Punjab; economic development; structural change; political economy